Mutations of the Platelet Thromboxane A2 (TXA2) Receptor in Patients Characterized by the Absence of TXA2–induced Platelet Aggregation despite Normal TXA2 Binding Activity - Higuchi, Wataru; Fuse, Ichiro; Hattori, Akira; Aizawa, Yoshifusa (Thrombosis and Haemostasis, 1999)
Previously, we reported five cases of platelet dysfunction characterized by the absence of thromboxane A2 (TXA2) – induced platelet aggregation despite normal TXA2 binding activity. In this platelet disorder, patients were divided into two groups; i.e. those whose platelets lacked or did not lack phospholipase C (PLC) activation (Group A and Group B, respectively) (Thromb Haemost 1996; 76: 1080). Furthermore, in one of the patients, we showed that a single amino acid substitution (Arg60 to Leu) in the first cytoplasmic loop of the TXA2 receptor (TXR) was responsible for this platelet disorder. However, mutational analysis of the TXR in the remaining patients has not been performed. Based on this background, we investigated the mutations of the TXR in these patients, and found that all of the patients have the same abnormality of the TXR (Arg60 → Leu), although the Group A patients were homozygous and the Group B patients were heterozygous for this mutation.This mutation is the only abnormality which has been found in this platelet disorder, and in patients heterozygous for this mutation, the mutant type TXR suppresses wild-type receptor-mediated platelet aggregation by a mechanism independent of PLC activation.
Keywords: Platelet dysfunction; thromboxane A2; receptor; point mutation